Digital forensics explained - Gogolin, Greg (Boca Raton : CRC Press, 2021)
This book covers the full life cycle of conducting a mobile and computer digital forensic examination, including planning and performing an investigation as well as report writing and testifying. Case reviews in corporate, civil, and criminal situations are also described from both prosecution and defense perspectives. Digital Forensics Explained, Second Edition draws from years of experience in local, state, federal, and international environments and highlights the challenges inherent in deficient cyber security practices. Topics include the importance of following the scientific method and verification, legal and ethical issues, planning an investigation (including tools and techniques), incident response, case project management and authorization, social media and internet, cloud, anti-forensics, link and visual analysis, and psychological considerations. The book is a valuable resource for the academic environment, law enforcement, those in the legal profession, and those working in the cyber security field. Case reviews include cyber security breaches, anti-forensic challenges, child exploitation, and social media investigations. Greg Gogolin, PhD, CISSP, is a Professor of Information Security and Intelligence at Ferris State University and a licensed Professional Investigator. He has worked more than 100 cases in criminal, civil, and corporate environments.
Includes index.
Previous edition: 2013.
1. What is digital forensics, and what should you know about it? 2. Digital forensic approaches and best practices 3. Digital forensics tool kit 4. Internet and e-mail examinations 5. Mobile forensics 6. Cloud computing and digital forensics 7. Law enforcement incident response 8. Report writing and presentation 9. Social media forensics 10. Social engineering forensics 11. Anti-forensics 12. Link and visual analysis 13. Psychological, ethical, and cultural implications of digital forensics 14. Someone is watching 15. The realities of digital forensic practice
OCLC-licensed vendor bibliographic record.
Keywords: Computer crimes -- Investigation; Computer security; Computer engineering; COMPUTERS / Security / General; LAW / Forensic Science; TECHNOLOGY / Electronics / Digital